Induction of oxygen vacancies in CuWO4 films used as photoanodes to improve the photocurrent and progesterone degradation efficiency - Silva, Rejane Maria P.; S. Costa, Gilson; R. Costa, Antônio Gabriel; S. Costa, Maria Joseíta; R. Santos, Luzia; S. Santos, Reginaldo (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
One of the biggest problems faced by humanity is the pollution of water resources by pollutants such as organic compounds such as polymers, herbicides, pesticides, dyes and medicines.[1] Studies show that several medications with estrogen and progesterone hormones pose risks to male fish and other aquatic organisms. The main problems caused by these hormones are decreased fertility, feminization of male organisms and hermaphroditism. Similar adverse effects are caused by these hormones also in humans, and these aqueous pollutants can alter the endocrine system and increase the risk of cancer.[2]  Photoelectrocatalytic technologies using metallic oxide semiconductors have received great attention owing to their potential and effectiveness in wastewater treatment. However, rapid recombination of the photogenerated electrons/holes (e−/h+) is the major drawback for this methodology.[3] Copper tungstate (CuWO4) is considered a semiconductor oxide with relatively short bandgap energy, ranging from 2.2 to 2.4 eV with excellent chemical stability over a wide pH range. However, CuWO4 presents a rapid recombination of photogenerated charges. Our research group has investigated strategies to improve charge transfer in CuWO4 films [4,5]. Oxygen vacancies (OVcs) in CuWO4 have also been induced as a way of altering the properties of this material.[6] In our study, OVcs were achieved through thermal treatment of the material in a gaseous atmosphere formed by a mixture of air/N2, in proportions of 0-100%. CuWO4 films with triclinic structure (Fig.1) were obtained by the drop-casting method on FTO-glass from a suspension prepared by polymer precursor method. The electrode thermally treated with an air/N2 ratio of 75% was the one with the highest photocurrent value. Photoelectrochemical measurements (Fig.2) carried out under polychromatic irradiation (100 mW cm-2) show that the CuWO4-75% films achieved a photocurrent of 40 µA cm-2. This value is approximately four times higher than the current observed for the unmodified CuWO4 film. This result indicates that N2 induces OVcs (Fig.3), due to the lower concentration of O2 during heat treatment and the growth of CuWO4 crystals. Thus, it can improve photocatalytic activity in the degradation of progesterone.